Features of schoolchildren’s psychophysiological adaptation to renewd educational program (Journal of Educational Sciences, 2020)
The researchers presented the results of a study of the level of psychophysiological adaptation to the updated curriculum of 2 schools with different levels of education. One of the most important stages of ontogenesis in adolescents is the inhibition of adaptive mechanisms associated with intense neurohumoral changes and the specific psychological content of this period. Peculiarities of adolescence can lead to an increase in the risk of adaptive disorders with adverse environmental influences. The increased educational load, especially in the case of various pedagogical innovations, imposes additional requirements on the adaptability of adolescents. In many physiological and hygienic studies, it was found that in the process of adaptation to educational activity, a deterioration in the functional state of the adolescent’s body is observed. To achieve the goal and objectives of the study, 56 students of 12-13 years of gymnasium No. 176 and secondary school No. 181 of Almaty were examined. In addition to quantifying the morphological state of adolescents, a study was carried out in all groups of the functional fund of the cardiorespiratory system. The research results were processed by the method of variation statistics according to the Student criterion. Key words: psychophysiology, teenager, adaptation, schoolchildren